Research on Operational Characteristics of Imported Rails under Conditions of East Siberian Railway; IOP Conference Series: Materials Science and Engineering; Vol. 127 : Urgent Problems of Modern Mechanical Engineering - Gizatulin R. A. Rinat Akramovich; Kozyrev N. A.; Valuev D. V. Denis Viktorovich; Valueva A. V. Anna Vladimirovna; Serikbol A. (2016, 2016)
Title screen